PERBANDINGAN PRODUKSI BUDIDAYA TANAMAN PADI DENGAN SALAH SATU JARAK TANAM ANJURAN DAN SISTEM BUDIDAYA PETANI - Untari Untari; Wahida Wahida (AGRICOLA, 2014)
Rice as main food crops especially for Indonesian people had higher attention from various parties. Their tried to improve the rice productivity to fulfil the people basic needs. The objectives of this research are 1) Comparing rice production between tiles cultivation techniques and spread cultivation techniques which farmers used; 2) Comparing the income levels of rice production between two cultivation techniques. The methodology used in this study is experimental. Rice cultivation data were tabulation and analyzed by comparing the rice production between tile and spread system. The variables that measured are filled grain and grain hollow, weight per panicle, weight of 1000 seeds and total production. The results showed that the number of filled grain for tile system is 108.48 grains while the spread system was 71.28 scatter seeds. Weight of 1000 seeds for tile system was equivalent to 22.57 g and for spread system was 22.03 g. Weight per panicle for tile system was 2.45 g  and for spread system was 1.65 g. Total rice production for tile system was 4.43 tonnes/ha while the spread system was 2.82 tonnes/ha. The income of farmers which used tile system was Rp. 26.58 million, - / ha while for spread system is Rp. 16.92 million, - / ha.